2004
DOI: 10.1124/jpet.104.071779
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Properties of Mixture of α-Amyrin and β-Amyrin Triterpenes: Evidence for Participation of Protein Kinase C and Protein Kinase A Pathways

Abstract: The mixture of the two pentacyclic triterpenes ␣-amyrin and ␤-amyrin, isolated from the resin of Protium kleinii and given by intraperitoneal (i.p.) or oral (p.o.) routes, caused dose-related and significant antinociception against the visceral pain in mice produced by i.p. injection of acetic acid. Moreover, i.p., p.o., intracerebroventricular (i.c.v.), or intrathecal (i.t.) administration of ␣,␤-amyrin inhibited both neurogenic and inflammatory phases of the overt nociception caused by intraplantar (i.pl.) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 32 publications
8
77
1
Order By: Relevance
“…), vehicle, 0.5 h before the i.pl. injection of 20 ml of capsaicin (1.6 mg/ paw) (Sakurada et al, 1993), BK (10 nmol/paw) , cinnalmaldehyde (10 nmol/paw) (Andrade et al, 2008), PMA (0.03 mg/paw) , or 8-bromocAMP (10 nmol/paw) (Otuki et al, 2005) into the ventral surface of the right hind paw. The amount of time spent licking the injected paw was recorded following the injection of one of the followings: capsaicin and cinnamaldehyde (5 min), BK, and 8-bromo-cAMP (10 min) or PMA (30 min).…”
Section: Formalin-induced Nociceptionmentioning
confidence: 99%
“…), vehicle, 0.5 h before the i.pl. injection of 20 ml of capsaicin (1.6 mg/ paw) (Sakurada et al, 1993), BK (10 nmol/paw) , cinnalmaldehyde (10 nmol/paw) (Andrade et al, 2008), PMA (0.03 mg/paw) , or 8-bromocAMP (10 nmol/paw) (Otuki et al, 2005) into the ventral surface of the right hind paw. The amount of time spent licking the injected paw was recorded following the injection of one of the followings: capsaicin and cinnamaldehyde (5 min), BK, and 8-bromo-cAMP (10 min) or PMA (30 min).…”
Section: Formalin-induced Nociceptionmentioning
confidence: 99%
“…These triterpenes have been reported to exert anti-inflammatory properties in various animal models, including colitis, cystitis or pancreatitis. [7][8][9] In the central nervous system, α-and β-amyrin have been reported to exhibit anti-nociceptive properties via the activation of cannabinoid receptors 10,11) and to exhibit antianxiety or anti-depression properties through the modulation of the benzodiazepine site of the γ-aminobutyric acid type A (GABA A ) receptor or noradrenergic receptor, respectively.…”
mentioning
confidence: 99%
“…Several types of mechanisms could be proposed, based on the phytochemical constituents of the plant, to explain the observed antinociceptive and anti-inflammatory activities. The antinociceptive activity of ACRE could be linked to the findings that flavonoids are potent inhibitors of protein tyrosine kinases (Oblak et al, 2000), the protein kinase C pathway (Otuki et al, 2005), and nitric oxide synthase type 2 (NOS-2) (Olszanecki et al, 2002), and have been shown to work via the l-arginine/NO pathway (Meotti et al, 2005). The protein tyrosine kinases, protein kinase C pathway, NOS-2, and l-arginine/NO pathway have been linked with antinociceptive (Ferreira et al, 1991;Machelska et al, 1997) as well as anti-inflammatory (Kim et al, 2004) activities.…”
Section: Discussionmentioning
confidence: 99%
“…Other than that, flavonoids also exhibit inhibitory effects against phospholipase A 2 and phospholipase C (Middleton et al, 2000), and cyclooxygenase and/or lipoxygenase pathways (Robak et al, 1998), which play an important role in the nociceptive and inflammatory processes. In addition, flavonoids exert their antinociception via opioid receptor activation, an activity that is not seen with triterpenes or saponins (Suh et al, 1996;Rajendran et al, 2000;Otuki et al, 2005). The anti-inflammatory activity of ACRE could be explained by the findings that flavonoids and triterpenes inhibit the nuclear factor-kappaB (NF-κB) (Nam, 2006).…”
Section: Discussionmentioning
confidence: 99%